Amelioration of lead (Pb) from contaminated soil using organic amendments (Bangladesh Journal of Scientific and Industrial Research, 2019)
Pot experiments were conducted at the department of Soil, Water and Environment, University of Dhaka to evaluate the effect of used tea leaves and poultry litter in ameliorating lead uptake and to alleviate toxicity of lead in Red amaranth (Amaranthus tricolor L.). The length, fresh weight and dry weight of shoot was decreased significantly by 34.83, 34.69 and 36.48%, respectively, in 200 mg kg-1 Pb treated pots compared to the control. The similar significant decreasing trend in case of macro nutrient concentration in shoot and root samples were also observed. %N, P, K, S, Mg and Ca concentration in edible parts (shoots) decreased by 66.3, 5.27, 52.17, 30.32, 61.54 and 62.87% in 200 mg kg1 lead (Pb) treated pots compared to the control. On the other hand Pb concentration in shoot and root was the highest at 200 mg kg-1Pb treated pots (55 and 189 mg kg-1 pot-1) and the lowest was in the control treatment (0.45 and 20 mg kg-1 pot-1). Biomass production were positively influenced by the application of organic amendments as well as lead uptake was significantly ameliorated into Red amaranth shoot and root due to application of used tea leaves and poultry litter which reduced soil to plant transfer (TrF) of Pb by 47.39, 56.34 and 16.67, 22.22% in shoots and roots of red amaranth, respectively, compared to the untreated pots.Bangladesh J. Sci. Ind. Res.54(2), 177-186, 2019